Developing Professionally - Khan, Rubina (Dhaka University Journal of Linguistics, 2009)
Teaching is a challenging job and teachers need to perform well in order to deliver their lessons effectively. One major prerequisite for effective performance is the need for teachers to engage in continuous professional development (CPD). Professional development (PD) includes a cluster of activities related to the enhancement of career growth and refinement of the skills of the practitioner. It may range from activities like attending pre-service and in-service training, participating in conferences, seminars, workshops, joining teacher associations, reading books and articles etc. This article briefly highlights the key ingredients of professional development, outlines the sources of PD and argues that professional development is essential for promoting individual and professional growth. Keywords: Professional Development (PD), Continuous Professional Development (CPD), Teacher Development (TD), knowledge base, ELT professional, facets of Continuous Professional Development. DOI: 10.3329/dujl.v1i2.3723 The Dhaka University Journal of Linguistics: Vol. 1 No .2 August, 2008 Page: 169-180